TEACHING YOUNG PEOPLE TO USE INNOVATIVE TECHNIQUES IN THE EDUCATIONAL PROCESS (Academicia Globe: Inderscience Research, 2023)
This article aims to explore the importance of incorporating innovative techniques in the educational process for young people. The article discusses various methods that can be used to promote innovative learning and provides insights into the results and benefits of using these techniques. The discussion also includes suggestions for educators to effectively implement innovative techniques in their teaching methods.